Asymptotic minimax risk in the uniform norm for the white noise model on the sphere - Jussi Klemelä (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
Estimation of the signal function defined on the unit sphere of the Euclidean space is considered. Gaussian continuous time white noise model is supposed. Uniform norm is chosen as a loss function and exact asymptotic minimax risk is derived extending the result of Korostelev (1993. The exact asymptotic minimax risk is given also for the L2-loss applying the result of Pinsker (1982).
urn:nbn:de:kobv:11-10056691
Keywords: 330; asymptotic minimax risk; spherical data; uniform norm; white noise model